Perfil metabólico e dinâmica folicular de cordeiras Santa Inês com consumo ad-libitum ou restrito de dieta com inclusão de soja grão tostada - Faria, Letícia Rodrigues (2020)
Feed restriction can compromise ovarian follicular development. Lipid supplementation, increases the energy content of the diet and acts positively on follicular dynamics and may be a strategy to reduce possible harmful effects of feed restriction on ovarian activity. The objectives of this study were to evaluate feed restriction and lipid supplementation as roasted whole soybeans on serum concentrations of linoleic acid, on metabolic profile and on follicular dynamics of Santa Ines ewe lambs that ovulated or not before ovarian assessments. Thus, we hypothesized that 1) ewe lambs fed with roasted soybean had greater concentration of linoleic acid in the blood, 2) lipid supplementation is positively related to follicular dynamics, 3) feed restriction compromises follicular development, 4) lipid supplementation with roasted whole soybeans reduces the harmful effects of feed restriction on follicular development and 5) ewe lambs having ovulation during the experimental period had better metabolic profile and enhanced follicular development than those no having ovulation. Thirty-five Santa Ines ewe lambs with 21.5 ± 1.7 kg of body weight and 95.0 ± 7.9 days of age, were randomly distributed in unbalanced block design with eight blocks with four animals and one block with three animals. Treatments were arranged in a factorial 2 x 2 x 2 based on level of intake (ad-libitum – AL or restricted – FR), on lipid supplementation (without or with lipid supplementation with roasted whole soybeans) and on the physiological status (absence or occurrence of ovulation). Diets were supplied to 37.4 ± 2.95 ± kg (mean ± standard deviation). The feed restriction was 15% of ad-libitum intake. Ovulation was detected by a serum progesterone concentration ≥ 1 ng/mL. The metabolic profile was assessed at 29.9 ± 0.56 and 35 ± 0.39 kg of body weight. Follicular dynamics were assessed at 30.7 ± 1.17 and 36.0 ± 0.91 kg of body weight at 17 ± 5 consecutive days in each occasion. The serum linoleic acid concentration was determined at 26-28, 28-32, 32-34 and 34-38 kg of body weight in AL-fed animals fed and FR-fed animals that consumed roasted whole soybeans. In the analyze of nutrients intake, average daily weight gain, feed conversion, blood metabolites, insulin, number of waves, number of follicles, diameter of the largest and second largest follicle and growth rate of the largest follicle, the intake level (ad-libitum or restricted) were considered, lipid supplementation and physiological status and the respective two- and three-way interactions. For the linoleic and stearic acid serum concentration, the treatment effect were considered. Dry matter intake was greater (P < 0.05) in unsupplemented-AL animals that ovulated compared to those not-ovulated; conversely, dry matter intake was lower in supplemented-AL animals that ovulated compared to those not-ovulated (three-way interaction, P < 0.05). Considering that supplemented-AL animals, those that not-ovulated had a greater ether extract intake (P < 0.05); while those ovulated had ether extract intake (intake level x lipid supplementation x physiological status interaction, P < 0.05). The average daily weight gain was lower (P < 0.05) in supplemented-AL animals that ovulated compared to those that not-ovulated. Feed conversion was lower (P < 0.05) in FR-fed than AL-fed animals. Glucose and triglyceride concentrations were higher (P > 0.05) in supplemented animals; while no changes were observed in the insulin concentration (P > 0.05). HDL and cholesterol serum concentrations were higher (P < 0.05) in unsupplemented-FR compared to AL-fed animals; while there was no difference between animals that received lipid supplementation (intake level x lipid supplementation interaction, P < 0.05). The HDL concentration was higher (P < 0.05) in the animals that ovulated compared to not-ovulated animals. Cholesterol concentration did not differ (P > 0.05) according to physiological status. Linoleic and stearic acid serum concentrations were not altered (P > 0.05) by intake level or lipid supplementation. The number of waves was higher (P < 0.05) in AL-fed than FR-fed animals. The main treatment effects, as well as the two- and three-way interactions were not significant (P > 0.05) for the number of follicles, diameter of the largest and second largest follicles and growth rate of the largest follicle. In conclusion, lipid supplementation with roasted whole soybeans improve the metabolic status, with no concomitant effect on linoleic acid blood concentration and on follicular dynamics. Except by reduction in number of waves, the follicular dynamics was not compromised by moderate feed restriction. Despite the higher HDL blood concentration in ovulated ewe lambs, these animals did not present enhanced follicular development.